2017
DOI: 10.3390/app7020118
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Resistance of Commercial Membrane Distillation Membranes in Waste Streams Containing Surfactants and Oil

Abstract: Water management is becoming increasingly challenging and several technologies, including membrane distillation (MD) are emerging. This technology is less affected by salinity compared to reverse osmosis and is able to treat brines up to saturation. The focus of MD research recently shifted from seawater desalination to industrial applications out of the scope of reverse osmosis. In many of these applications, surfactants or oil traces are present in the feed stream, lowering the surface tension and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Especially, when the VOCs are alcohol or having surfactant properties, membrane wetting will occur and lead to further deterioration of the permeate quality as the feed water can pass through the membrane directly via the wetted pores [11][12][13]. Recently, some researchers studied the effect of the surfactant and oil existed in the produced water on the water recovery via MD and found that they had strong negative impact on the permeation flux and permeate quality [12,14]. However, none of researches have investigated the effect of VOCs in the produced water on the MD performance, which may share similar effects as the surfactant and oil.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, when the VOCs are alcohol or having surfactant properties, membrane wetting will occur and lead to further deterioration of the permeate quality as the feed water can pass through the membrane directly via the wetted pores [11][12][13]. Recently, some researchers studied the effect of the surfactant and oil existed in the produced water on the water recovery via MD and found that they had strong negative impact on the permeation flux and permeate quality [12,14]. However, none of researches have investigated the effect of VOCs in the produced water on the MD performance, which may share similar effects as the surfactant and oil.…”
Section: Introductionmentioning
confidence: 99%
“…The PI membranes showed a higher electrolyte uptake capability than that of the commercial PE membrane (with a water contact angle over 95 ), which may be due to their higher porosity and hydrophilicity. 36,37 The hotpress-induced PI membrane showed a higher electrolyte uptake efficiency than that of the thermally-treated PI membrane because of the higher porosity, along with the dense, uniform arrangement of the nanobers. The thermal behaviors of the commercial PE, neat PAA, and PI membranes were monitored by TGA under the N 2 environment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These hydrophobic membranes are characterized by the water contact angles and liquid entry pressures (LEP). The contact angles for PP 0.45 micron (Franken et al 1987) and PTFE membranes are greater than 100ᵒ (Eykens et al 2017) corresponding to hydrophobic surfaces. The operating pressure differences of the MD system were kept well below the LEP values in our MD tests.…”
Section: Conditionmentioning
confidence: 92%